Impact of consumer preference on the decision-making of prefabricated building developers - Han, Yanhu; Xu, Xiaobo; Zhao, Yu; Wang, Xiaoping; Chen, Zeyu; Liu, Jia (Journal of Civil Engineering and Management, 2022)
Customers’ preferences for prefabricated building or conventional cast-in-situ building directly affect the decision-making process for strategic selection of building developers. This study utilizes a Hotelling model integrating game theory, including the market share function, product price function, and profit function of duopoly building developers to contribute a new approach to assist decision makers in their selection of developers for their projects. By analyzing different strategy combinations and the income matrix, we obtained the strategy combinations of duopoly building developers and the income matrix strategies, market share, optimal price and maximum profit. Managerial implications were discussed for government and building developers. Finally, we presented the research contribution as well as future research direction.